Variability of fibrinogen measurements in post-myocardial infarction patients - Baumert, Jens; Karakas, Mahir; Greven, Sonja; Rückerl, Regina; Peters, Annette; Koenig, Wolfgang (Thrombosis and Haemostasis, 2012)
Elevated fibrinogen levels are strongly and consistently associated with incident coronary heart disease (CHD). A possible causal contribution of fibrinogen in the pathway leading to atherothrombotic cardiovascular disease complications has been suggested. However, for implementation in clinical practice, data on validity and reliability, which are still scarce, are needed that are still scarce, especially in subjects with a history of CHD. For the present study, levels of plasma fibrinogen were measured in 200 post-myocardial infarction (post-MI) patients aged 39–76 years, with approximately six blood samples collected at monthly intervals between May 2003 and March 2004, giving a total of 1,144 samples. Inter-individual variability (between-subject variance component, VCb and coefficient of variation, CVb), intra-individual and analytical variability (VCw+a and CVw+a), intraclass correlation coefficient (ICC) and the number of measurements required for an ICC of 0.75 were estimated to assess the reliability of serial fibrinogen measurements. Mean fibrinogen concentration of all subjects over all samples was 3.34 g/l (standard deviation 0.67). Between-subject variation for fibrinogen was VCb = 0.34 (CVb,=17.5%) whereas within-subject and analytical variation was estimated as VCw+a = 0.14 (CVw+a=11.0%). The variation was mainly explained by between-subject variability, shown by the proportion of total variance of 71.3%. Two different measurements were required to reach sufficient reliability, if subjects with extreme values were not excluded. The present study indicates a fairly good reproducibility of serial individual fibrinogen measurements in post-MI subjects.
Keywords: Myocardial infarction; fibrinogen; cardiovascular risk factors; biological variation; number of measurements